PLD programmer using PC / Rossilawati Abdul Hayet - Abdul Hayet, Rossilawati (1997)
This project explores the hardware and software development for programming of programmable logic ICs. The objective of the project is to design a programmer circuit and develop the software to be able to programme the programmable logic device (PLD) by using personnel computer(PC). In this case EPROM family are selected as a case study. The types of EPROM that has been tested are 27256,27128 and 2764. When the input is given to this circuit, it will be automatically tested using the QBASIC software. Then it will give the result. QBASIC is also used to communicate between the programmer circuit and the PC by using serial data transfer technique.